Risk factors for visual impairment and blindness amongst black adult diabetis receiving treatment at Government healthcare facilitis in Mopani District, Limpopo province, South Africa - Raymond G. Mabaso; Olalekan A. Oduntan (AOSIS, 2014)
Background: Diabetes mellitus (DM) is a common systemic disease amongst Black South Africans. It may lead to diabetic retinopathy (DR), a common cause of visual impairment (VI) and blindness. DR may signifiantly increase the prevalence of VI and blindness. Aim: To assess risk factors for VI and blindness amongst a black diabetic South African population aged ≥ 40 years. Setting: The study was conducted in seven Government healthcare facilities (two hospitals, four clinics and one health centre) in Mopani District, Limpopo province, South Africa. Methods: This was a cross-sectional health facility-based quantitative study. Structured interviews were used to obtain information, which included sociodemographic profie, knowledge about DM and its ocular complications, presence of hypertension and accessibility to health facilities. Subsequently participants were examined for VI and blindness using an autorefractor, pinhole disc, ophthalmoscope and logMAR visual acuity chart. Anthropometric measurements (height, weight and waist) were also taken. Associations between 31 risk factors and VI as well as blindness were statistically examined. Results: Participants (N = 225) included 161 women and 64 men aged 40-90 years (mean 61.5 ± 10.49 years); 41.3% of them had VI and 3.6% were blind. Cataracts (76.8%) and DR (7.1%) were the common causes of compensated VI and blindness. Risk factors that were associated with VI and blindness were age, monthly income, compliance with losing weight and physical activity. Conclusion: Findings suggest that lifestyle intervention and appropriate eyecare programmes may reduce VI and blindness in this population.